Characterization of ion-exchange resins under thermal loading - Zárybnická, Lucie; Stránská, E.; Machotová, Jana; Černošková, Eva; Melánová, Klára (My University, 2016)
The present work deals with the influence of temperature on the ion-exchange capacity of selected ion-exchangers. Technological operations running at elevated temperatures (drying, homogenization) can influence ion-exchange capability of ion-exchangers, which may affect values of the ion-exchange capacity. Several types of anion and cation-exchangers have been chosen for its application in practice. It was shown that the optimum processing temperature for anion and cation-exchange resins is in the range of 101-115 °C.
Charakterizace iontovýměnných pryskyřic za zvýšených teplot
Keywords: ion-exchange resins; ion-exchange capacity; thermal loading; anion-exchange resin; cation-exchange resin; iontovýměnné pryskyřice; iontovýměnná kapacita; tepelné namáhání; anionvýměnná pryskyřice; kationvýměnná pryskyřice